2014
DOI: 10.1108/ss-02-2013-0015
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for integrating design and construction and operations and maintenance supply chains in Singapore

Abstract: Purpose -The purpose of this paper is to investigates strategies for achieving better integration between the design and construction (DC) and operation and maintenance (OM) supply chains in Singapore. The specific objectives are to: discover the goals that stakeholders want to achieve in integrating the supply chains; identify the stakeholders that play important integration role in each supply chain; and investigate the effective strategies that may yield better integration of the supply chains. Design/metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…This fact outlines implications for future compositions of BIM-enabled SC partnerships, as probably architects could be deemed important actors for the formation of future BIM-enabled SC partnerships. Although Ling et al (2014) underline that the client and contractor are drivers of SC integration, the design team is similarly the driver of design innovation for a project (Elmualim & Gilder, 2014). This is corroborated from diagram b in Figure 20, where it is obvious that the architect is the driver of the generation of building information.…”
Section: Coordination Mechanismsmentioning
confidence: 77%
See 1 more Smart Citation
“…This fact outlines implications for future compositions of BIM-enabled SC partnerships, as probably architects could be deemed important actors for the formation of future BIM-enabled SC partnerships. Although Ling et al (2014) underline that the client and contractor are drivers of SC integration, the design team is similarly the driver of design innovation for a project (Elmualim & Gilder, 2014). This is corroborated from diagram b in Figure 20, where it is obvious that the architect is the driver of the generation of building information.…”
Section: Coordination Mechanismsmentioning
confidence: 77%
“…The strategic -or internal -SC partners of the case are the client, the contractor, and two installation companies. This team composition is considered representative given that the client and the contractor are usually the main drivers of SC integration (Ling, Toh, Kumaraswamy, & Wong, 2014). The contractor is additionally linked with separate long-term partnerships with a structural engineer, with whom they have numerous previous collaborations, and another installation company.…”
Section: Case Descriptionmentioning
confidence: 99%
“…CSCs are thus unstable, fragmented, and cannot be completely repeated [7]. Despite numerous studies in the field of CSCM, challenges associated with information exchange [8], the lag of knowledge transfer [9], inefficient cooperation [10], the conflicts of interest among stakeholders remain [11]. Therefore, the research gaps and cutting-edge research directions in CSCM research need to be identified by sorting out the existing CSCM research results with a holistic understanding of the current state of research in the field.…”
Section: Introductionmentioning
confidence: 99%